Locating the CAP in an escalating green agenda - David Baldock (Italian Review of Agricultural Economics (REA), 2020)
Since the advent of decoupling, the process of adapting the Common Agricultural Policy (CAP) to a rising set of environmental priorities has involved various approaches and technical adjustments, with most Member States inclined to move more slowly than the European Commission. The debate on the post 2020 incarnation of the CAP has revealed a continued preference for gradual adaptation which stands in contrast to the escalation of environmental ambition set out in the Commission's recent initiatives stemming from the Green Deal, including the Farm To Fork Strategy. Different ways of resolving this tension are discussed and some of the implications for the CAP and the related question of the distribution of EU funds to the Member States considered.
Keywords: Q150; Q180; Q58; 330; agricultural policy; agriculture and environment; CAP reform; climate policy; environmental public goods; EU budget; European Green Deal; Farm to Fork Strategy